Records of the rare deep-sea threetooth puffer fish, Triodon macropterus (Tetraodontiformes: Triodontidae) from Molucca and Sawu seas, Indonesia - Kunto Wibowo; Miftahul Huda; Rachmad Sholeh Wicaksono; Monica Bataona; Teguh Peristiwady (Jurnal Iktiologi Indonesia, 2020)
The Indo-West Pacific species of rare deep-sea threetooth puffer fish, Triodon macropterus Lesson 1931 was recorded on the basis of two voucher specimens from southern coasts of Lembeh Island, North Sulawesi, Molucca Sea and Solor Island, Sawu Sea and a photograph of fresh individual after captured from Sawu Sea. In Indonesia waters, the species has previously been known only from Banda Sea, thus the specimens and a photograph in this study represent the first records of T. macropterus from Molucca Sea and Sawu Sea. Abstrak Spesies ikan langka laut dalam Triodon macropterus Lesson 1831 yang mempunyai distribusi di perairan Indo Pasifik Barat, dijumpai di perairan lepas pantai selatan Pulau Lembeh, Sulawesi Utara, Laut Maluku dan lepas pantai selatan Pulau Solor, Laut Sawu, Indonesia berdasarkan identifikasi dari dua koleksi ilmiah spesimen dan sebuah foto individu sesaat setelah tertangkap. Di perairan Indonesia, spesies ini sebelumnya hanya diketahui tercatat dari Laut Banda, sehingga spesimen dari selatan Pulau Lembeh dan selatan Pulau Solor serta koleksi foto dalam studi ini merupakan catatan pertama distribusi T. macropterus dari Laut Maluku dan Laut Sawu.